Parents and partners: Moderating and mediating influences on intimate partner violence across adolescence and young adulthood. (December 2017) - Kaufman-Parks, Angela M.; DeMaris, Alfred; Giordano, Peggy C.; Manning, Wendy D.; Longmore, Monica A.
Prior work examining intimate partner violence (IPV) among young adults often has emphasized familial characteristics, such as parent–child physical aggression (PCPA), and romantic relationship dynamics, such as jealousy and controlling behaviors, but has not considered these two domains simultaneously. Likewise, research examining how these two domains affect IPV perpetration over time for young adults is still limited. Using five waves of data from the Toledo Adolescent Relationships Study ( N = 950), the present study examined the influence of parent–child relationship factors and romantic relationship dynamics in both their main and interactive effects on IPV perpetration spanning adolescence through young adulthood. Results from random-effects analyses indicated that both familial and romantic relationship dynamics should be taken into account when predicting IPV perpetration. Importantly, these two domains interacted to produce cumulatively different risk for engaging in violence against a romantic partner. Individuals were more likely to perpetrate IPV when their romantic relationship was characterized by verbal aggression if they reported PCPA experiences.